Nahdlatul Ulama Theological Basis in Accepting the Concept of Guided Democracy 1959-1965 - Andri Nurjaman; Arzam Arzam; Muhamad Yusuf; Doli Witro; Anwar Musadad (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
Nahdlatul Ulama is the only major political party representing Muslims in national politics during the implementation of guided democracy. NU's accommodative and flexible political practices have made Nahdlatul Ulama able to live and continue to survive in difficult times. This is inseparable from NU's religious political strategy, which is its guideline. The theological basis based on the theory of fiqh and ushul fiqh can be seen in NU's acceptance of the guided democracy concept. This paper aims to reveal NU's theological foundation in accepting the concept of guided democracy. Data was collected through the study of texts and manuscripts and literature studies. The data analysis technique uses hermeneutic theory to capture symbols in the form of texts originating from Islamic law, namely fiqh, and ushul fiqh, as the basis and foundation of NU accepting guided democracy. The results showed that there were several theories of fiqh and ushul fiqh used by NU, including the concepts of maslahah and mudarat, dar’ul mafasid muqoddamun ala jalbil mashalih, amar ma’ruf nahyil mungkar, ma la yudraku kulluh la yutraku kulluh, al-muhafadthu ala qodim al-shahih wa al-akhdzu bi al-jadid al-ashlah, and the concept of syuro presented by KH Idham Chalid.